Linear dependence of powers of linear forms - Sładek, Andrzej (Annales Mathematicae Silesianae, 2022)
The main goal of the paper is to examine the dimension of the vector space spanned by powers of linear forms. We also find a lower bound for the number of summands in the presentation of zero form as a sum of d-th powers of linear forms.